Takhrij and Syarah Hadith of Agrotechnology Farming in Dry Land - Dandi Guntur Apriandi; Wahyudin Darmalaksana; Sofiya Hasani (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about farming on dry land. This research method is qualitative through the takhrij and syarah hadith approaches with agrotechnological analysis. The result and discussion of this research is that ultisol soil has high potential for the development of dry land agriculture, but the constraints in the use of this land if it is not managed properly can inhibit plant growth, especially food crops. The conclusion of this research is takhrij and syarah hadith of the Prophet. about farming on dry land with ultisol soil media has a high potential for the development of dry land agriculture.